"The mother I was born to or the one I worked for?": An exploratory study on family separation in live-in child domestic workers in Karnataka, India. (July 2021) - Ramanan, Namratha; Adriaenssens, Peter; Derluyn, Ilse; De Haene, Lucia
Abstract: Background: Live-in child domestic work is a mostly exploitative informal labour sector that involves child migration and long-term, most often forced separation from family and extended family network. This is the first empirical exploration of children's lived experiences of ongoing family-child separation in the context of child domestic work. Objective: While numerous studies conducted on childhood, child development and child health in the context of child labour argue that family separation is detrimental to children's psychosocial health, little is known about how this separation is understood by children living through ongoing separation while being employed in child domestic work. This study aimed at an empirical exploration of how child domestic workers experience the impact, meaning of, and coping with family separation in the context of child domestic work. Participants and setting: 10 children (10–14 years old) working as live-in domestic help in Karnataka, India. Methods: Data collection for this small-scale, exploratory qualitative study consisted of the administration of consecutive (2–3) task-based narrative interviews, involving graphic elicitation and doll-play techniques, with live-in child domestic workers. Results: Findings from children's narrative accounts indicate how they relate ongoing family separation to cultural meaning systems regarding filial duty, family cohesion, and the role of the extended family network as a way of understanding, living and coping with family-child separation in the face of the stressors of live-in child domestic work. Conclusions: This paper generates an explorative understanding of how children make meaning of family separation, and their perspectives on re-uniting with their families. It also aims to aid organizations in designing family re-integration protocols based on perspectives gleaned from the children.